Two functional indel polymorphisms in the promoter region of the Brahma gene (BRM) and disease risk and progression-free survival in colorectal cancer. - Yajun Yu; Dangxiao Cheng; Patrick Parfrey; Geoffrey Liu; Sevtap Savas (PLoS ONE)
Background and objective The Brahma gene (BRM) encodes a catalytic ATPase subunit of the Switch/Sucrose non-fermentable (SWI/SNF) complex, which modulates gene expression and many important cellular processes. Two indel polymorphisms in the promoter region of BRM (BRM-741 and BRM-1321) are associated with its reduced expression and the risk of susceptibility or survival outcomes in multiple solid cancers. In this study, we have examined these variants in relation to susceptibility and survival outcomes in colorectal cancer. Methods Genotypes were obtained using TaqMan assays in 427 cases and 408 controls. Multivariate logistic and Cox regression models were fitted to examine the associations of the BRM-741 and BRM-1321 genotypes adjusting for relevant covariates. Sub-group analyses based on tumor location and patient sex were also performed. In all analyses, indels were examined individually as well as in combination. Results Our results showed that there was no association between the BRM polymorphisms and the risk of colorectal cancer. However, genotype combinations of the BRM-741 and BRM-1321 variants were associated with the risk of colon cancer. Particularly, patients having at least one variant allele had increased risk of colon cancer when compared to patients with the double wild-type genotype. In the survival analyses, BRM-741 heterozygosity was associated with longer progression-free survival time in the colorectal cancer patients. A stronger association was detected in the male patients under the recessive genetic model where the homozygosity for the variant allele of BRM-741 was associated with shorter progression-free survival time. Conclusions Our analyses suggest that BRM-741 and BRM-1321 indels are associated with the risk of developing colon cancer and the BRM-741 indel is associated with the disease progression in colorectal cancer patients, especially in the male patients. Although our results show a different relationship between these indels and colorectal cancer compared to other cancer sites, they also suggest that BRM and its promoter variants may have biological roles in susceptibility and survival outcomes in colorectal cancers. Performing further analyses in additional and larger cohorts are needed to confirm our conclusions.